Islam Kaffah dan Relevansinya dengan Masyarakat Indonesia yang Plural dalam Perspektif al-Qur’an - Ruston Nawawi (UIN Kiai Haji Achmad Siddiq Jember, 2021)
Islam is a religion that is syâmil (covering everything) and Kamil (perfect). As a religion that is shahil, Islam explains everything and regulates all matters: aqeedah, worship, morals, food, clothing, muamalah, ‘uqûbât (legal sanctions), and others (QS. An-Nahl [16]: 89). Islam was brought by the Prophet Muhammad in order to guide his people to a straight path so that people will survive in the world and the hereafter. Islam is not only confession but more important is how in daily life and behavior in accordance with the provisions set by shari’a. Humanity consists of various nations and tribes that have different skin colors, languages, customs, and tendencies. To be able to live together in a state of peace and prosperity and be able to work together and help fellow human beings and can maintain unity (ukhuwah) among Muslims.